2, 4-Diarylquinolines: Synthesis, Absorption and Emission Properties. (April 2014) - Adeloye, Adewale O.; Mphahlele, Malose J.
The absorption and emission spectra of series of 2, 4-diarylquinolines prepared via palladium catalysed Suzuki-Miyaura cross-coupling of 2-aryl-4-chloroquinolines with arylboronic acids were measured in solution to understand the influence of substituents on intramolecular charge transfer.